2011
DOI: 10.5624/isd.2011.41.4.167
|View full text |Cite
|
Sign up to set email alerts
|

Ellis-van Creveld syndrome in an Indian child: a case report

Abstract: Ellis-van Creveld syndrome is a rare congenital genetic disorder having autosomal recessive inheritance. It is a syndrome affecting the Amish population of Pennsylvania in USA with prevalence rate of 1/5,000 live at birth. In non-Amish population, the birth prevalence is 7/1,000,000. The syndrome is characterized by bilateral postaxial polydactyly of the hands, chondrodysplasia of long bones resulting in acromesomelic dwarfism, ectodermal dysplasia affecting nails as well as teeth and congenital heart malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 6 publications
2
38
1
3
Order By: Relevance
“…También se informaron varios casos en la India. [6][7][8] Cabe destacar que la madre y el padre del paciente provenían de una población de la selva peruana.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…También se informaron varios casos en la India. [6][7][8] Cabe destacar que la madre y el padre del paciente provenían de una población de la selva peruana.…”
Section: Discussionunclassified
“…1,2 El fenotipo es variable y afecta múltiples órga-nos. Sus características clínicas se describieron en numerosos informes [3][4][5][6] y series de casos. [7][8][9][10][11][12] Después del nacimiento, el cuadro clínico suele ser la tétrada conformada por: 1) estatura pequeña con acortamiento de la parte distal de los miembros y acortamiento de las falanges media y distal; 2) polidactilia en las manos (casi siempre bilateral), que ocasionalmente afecta los pies; 3) displasia condroectodérmica que afecta principalmente las uñas, el cabello y los dientes, y 4) malformaciones cardíacas congénitas (50% a 60% de los casos); las más frecuentes son defectos septales y aurícula única; también se han informado defectos de las válvulas mitral y tricúspide, persistencia del conducto arterioso y síndrome del corazón izquierdo hipoplásico.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[15] Though no defi nitive cure for EVC syndrome, eff ective management requires multidisciplinary approach such as clinical geneticist, cardiologist, orthopedician, physical and occupational therapist and since oral manifestation is one of the characteristic diagnostic features, the dentists play a major role in management of this syndrome related to esthetics and growth of the jaws. [16] Invasive dental procedures should be done under antibiotic prophylaxis. The removal of natal teeth should be done as they may impair the feeding.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In 1964, McKusick et al, reported a large number of cases in the Amish community of Lancaster country, Pennsylvania USA with prevalence rate of 1/50,000 live birth. [2] In nonAmish population, the estimated birth prevalence is 7/1,000,000. Around 150 cases are described in literature and not more than 25 cases have been reported in India.…”
Section: Introductionmentioning
confidence: 99%